2012
DOI: 10.1371/journal.pone.0039712
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Use of Insecticide Treated Nets for the Prevention of Malaria in Pregnancy: Jinja, Uganda

Abstract: BackgroundOne established means of preventing the adverse consequences of malaria during pregnancy is sleeping under an insecticide treated net (ITN) throughout pregnancy. Despite increased access to this intervention over time, consistent ITN use during pregnancy remains relatively uncommon in sub-Saharan Africa.Methodology/Principal FindingsWe sought to identify determinants of ITN use during pregnancy. Utilizing a population-based random sample, we interviewed 500 women living in Jinja, Uganda, who had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
44
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 35 publications
8
44
1
Order By: Relevance
“…The respondents stated reasons such as discomfort due to heat from the net and difficulty of hanging the nets as challenges in using ITNs. These observations are similar to findings in other studies in Africa [14, 20, 2629]. More aerated materials other than polyester may help to enhance ventilation through hung ITNs.…”
Section: Discussionsupporting
confidence: 91%
“…The respondents stated reasons such as discomfort due to heat from the net and difficulty of hanging the nets as challenges in using ITNs. These observations are similar to findings in other studies in Africa [14, 20, 2629]. More aerated materials other than polyester may help to enhance ventilation through hung ITNs.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies reported similar findings [7,18,19], while the others showed significant associations between socio-economic factors and ITN use [11,12]. The presence of prominent vector breeding site yielding varying risk to the households in the study area was worthy of note since the households located closer to the vector breeding site reported more frequent use of ITNs, implying influence of nuisance mosquitoes and/or risk perception might have outweighed factors such as education and wealth, with regard to sleeping under ITNs.…”
Section: Discussionsupporting
confidence: 64%
“…to medicate without clinical symptoms, testing and diagnosis, particularly against a backdrop of Test Treat and Track for malaria [16]. A patient’s own decision-making around treatment can be complex and challenging [17], as can that of a patient’s or child’s caregiver [18] despite being ‘risk aware’, and motivated towards their welfare. Values such as a caregiver’s priorities (work vs. ensuring a child is well), life philosophy (treat to protect), self-efficacy (perceived ability) and background (malaria is a risk presented to all) are all likely to contribute to decision-making [17].…”
Section: Discussionmentioning
confidence: 99%